(untitled) (Scientific Journal of Eduardo Mondlane University, Serie: Educational Sciences, 2012)
The aim of this paper is to examine and understand the concept of ethics as adopted in the teaching of philosophy in high schools in Mozambique in order to "address" what is officially termed as moral deficit, prevailing among students at the said level of education. The methodology revolves around a discussion of the literature review on different modalities of inclusion of ethics in school education - as a crosscutting issue as well as a topic for of the study of Philosophy. Further, the place of Ethics in the teaching of philosophy in Mozambique is explained based on official documents and speeches and on respondents who were interviewed and sounded about the reintroduction of Philosophy into the Mozambican High Schools. The results showed that the conception of Ethics that was adopted based on a person and in persuit to overcome the “moral deficit" is diffuse. Furthermore, it became evident that there is an internal contradiction between the content, the proposed teaching methodologies for the approach towards the teaching of Ethics and Philosophy and what is said by the interviewed intellectuals, given that the methodological orientations point to a prescriptive and disciplinary Ethics. Thus, from an Ethics affirmed as the means through which a philosophical reflection on morality is carried out, the current conception of ethics in the newer training program of philosophy in high schools leans more towards the provision of a moral education.